PERILAKU PENGGUNAAN MEDIA MASSA PADA MASYARAKAT PERDESAAN - Leadya Raturahmi (Jurnal Riset Komunikasi, 2018)
This research is conducted because of the presence of mass media technology into the life of rural communities. This study aims to determine the behavior of media mass media use to audiences in rural areas in the form of intensity and context of use related to media skills.This research is a quantitative descriptive research using data collection technique through survey method / questionnaire. Population in research is permanent resident of Sekarwangi Village Garut Regency which have been aged 17 years and over, that is 3,853 people. Through random sampling, 251 respondents were obtained. The results of this study indicate that the intensity of mass media usage in rural audiences in using mass media is in level 4 that is capable and understand the purpose of use in using mass media, especially on the main mass media commonly accessed is television and radio. On internet usage, rural audiences are in level 2 that few are capable of using internet. In the context of use, the media audiences in rural areas are in level 4 that is knowing, understanding and have little ability to anticipate the negative impact on the use of mass media. But the media audiences do not yet have the skills to relay their opinions through the mass media. It can be concluded that the mass media audiences in rural areas have been able to connect their wishes, experiences, and hopes for the use and benefits received from the mass media, though not yet able to recharge their understanding of the mass media message.